Carving a Space for Elite Republicanism: Hierarchy, Deference and Paternalism in American Political Development - O'Hara, Jonathan (Europolis, Journal Of Political Science And Theory, 2010)
The present article is a review of the American Political Development literature dealing with the issue of national administrative politics and development in late nineteenth century American history. Particular attention is paid to the ways in which historical institutionalists discount the importance of elite republican ideology as an explanation of national administrative growth. Attention is also paid to the ways in which sociological institutionalists view republicanism as a viable ideological alternative only for far flung and marginalized social interest groups. The article argues for studying the ideology also in terms of its elitist tradition and the tradition’s application to national administrative politics and development in the American context, emphasizing categories of hierarchy, deference and paternalism. As a review of seminal works related to the research program of American Political Development, this article is of particular use to those studying American development at the turn of the twentieth century.
Keywords: American politics; United States; dept.psc; elitism; ideology; republicanism